Functions of Music Festivals in Modern Italy: “Rossini Opera Festival” - Ponomarenko, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
The relevance of the study. Considering the music festivals of modern Italy, it is important to identify their functionality and influence on the development of the cultural life of the country as a whole. This issue has been little studied, although, in our opinion, it is important and relevant for characterizing the festival movement in Italy. Main objectives of the study is to describe the International Opera Festival “Rossini Opera Festival: ROF”, its main functions. The methodology is based on the use of the inductive method, which, to characterize the festival process in the cultural life of Italy, involves the study of individual festival projects and provides for the use of a set of complementary research methods — historical-analytical, empirical and sociocultural. The historical-analytical method contributed to the understanding of the logic of the formation and development of the festival, the appeal to empirical and sociocultural methods made it possible to consider the features of the organization of the festival in the context of social relations in the system of music life in modern Italy. Results and conclusions. As an instrument of dialogue between civilizations, music is still today a fundamental lever of economic growth, able to interact with all other values: artistic heritage, cultural and tourism industry, environment and landscape. Through an integrated plan of structural interventions, services for citizens and businesses of the city, music in Pesaro becomes an engine of development, creative enrichment of cultural heritage and synergy between culture, tourism, society and education. The "Rossini Opera Festival: ROF" is a truly local indie phenomenon that draws a prepared and interested audience to Pesaro. Music as a means of dialogue between civilizations today contributes to economic growth, interaction with all other values of the region: historical and artistic heritage, cultural, tourism industry, landscape. Impressive is not only the scale of the project, but also the effectiveness of cooperation between cultural, financial, state institutions participating in its organization. Together they have developed a formula for holding Italian festivals, which provides a high result — the revival of the cultural and economic development of the region thanks to tourist flows, changing the image of cities (creating new infrastructure), interaction between public and private institutions, local authorities, professionals and art lovers. As an inseparable component of human culture, music always, in all its manifestations, acts as its memory, as a memory of history, a reminder of past events and their participants.